Crystallization behavior and toughening mechanism of poly(ethylene oxide) in polyoxymethylene/poly(ethylene oxide) crystalline/crystalline blends. (16th April 2014) - Liu, Yongcheng; Zhou, Tao; Chen, Zhengguang; Li, Lin; Zhan, Yanhui; Zhang, Aiming; Liu, Feiwei
<x xml:space="preserve">Abstract</x> In this study, the unique crystallization behavior of poly(ethylene oxide) (PEO) in polyoxymethylene (POM)/PEO crystalline/crystalline blends was examined in detail. This study was the first to report the typical fractionated crystallization of PEO in POM/PEO blends when PEO is fewer than 30 wt.%. The delayed crystallization temperature of PEO was confirmed at about 5°C to 14°C by using differential scanning calorimetry and perturbation–correlation moving‐window 2D correlation IR spectroscopy. Wide‐angle X‐ray diffraction indicates that no new crystal structures or co‐crystals were generated in POM/PEO. The statistical calculations of scanning electron microscopy photos show that the average diameter of PEO particles is 0.227 µm to 1.235 µm and that the number of small particles is as many as 109 magnitudes per cm3. Theory analysis establishes that the delayed crystallization of PEO is a heterogeneous nucleation process and not a homogeneous nucleation process. A significant toughening effect of PEO to POM was also observed. The impact strength of POM/PEO acquires a maximum of 10.5 kJ/m2 when PEO content is 5%. The impact strength of the blend increases by 78.0% compared with pure POM. To improve the toughening effect, the best particle size is established between 0.352 and 0.718 µm, with a PEO particle spacing of 0.351 µm to 0.323 µm. The number of corresponding particles was 0.887 × 109 per cm3 to 3.240 × 109 per cm3. A PEO toughening model for POM was proposed to provide a new and effective way to solve the problem of POM toughening. Copyright © 2014 John Wiley & Sons, Ltd.